PARTISIPASI PEMUDA DALAM PEMBANGUNAN DESA DI KELURAHAN BUDAYA PAMPANG KECAMATAN SAMARINDA UTARA KOTA SAMARINDA - Priscky Laurance Rampengan (Magister Administrasi Publik FISIP Universitas Mulawarman, 2020)
This study aims to describe the participation of youth in rural development as well as supporting and inhibiting factors of youth participation in village development in the cultural village of Pampang in the northern Samarinda district of Samarinda city. The research method used in this research is descriptive qualitative. Data analysis using interactive model analysis. This study aimed at youth participation in the development of Pampang culture villages was still not optimal. Youth are only allowed to give proposals or ideas in development planning. However, youth's ideas and proposals were taken into account, and young people desire to be involved in all development activities because they will continue the cultural heritage and development going forward.Keywords: Participation, Youth, Development